Evaluation of the Suitability of Yafran Clays for the Manufacture of Building Bricks - Eng. Laila Massaud El-Mazugha; Dr. Abdelsalam Mohamed Madi; Dr. Hatim Abdullah Issa; Eng. Mohamed Khaled Alturki; Eng. Safaa Al-Bashir Al-Shushan; Eng. Asma Mohammed Al-Najjar (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to assess the suitability of clay from the Yefren area in the Nafusa Mountains, Libya, for the production of fired bricks by evaluating its physical, chemical, and mineralogical properties. The methodology involved collecting field samples and conducting laboratory tests to determine moisture content, specific gravity, liquid and plastic limits, compressive strength, and water absorption rate. Additionally, X-ray diffraction (XRD) analysis was performed before and after thermal treatment at 900°C. The results indicated that the clay exhibits favorable physical characteristics, with a moisture content of 36.8%, specific gravity of 2.6, and good plasticity reflected by a plasticity index of 45%. The produced bricks showed a compressive strength of 9 MPa and a water absorption rate of 11.6%, which falls within acceptable limits. Chemically, the clay contains adequate proportions of silica (70.63%), alumina (9.12%), as well as suitable levels of iron and calcium oxides, supporting its potential for industrial application. Mineralogical analysis revealed the presence of clay minerals such as kaolinite and illite, with thermal stability maintained after firing—enhancing the clay’s suitability for high-quality brick manufacturing. The study recommends further mineralogical analysis of additional samples and testing under various firing temperatures to optimize the final product quality.